Mathematical Model of Functional Respiratory System for the Investigation of Harmful Organic Compounds Influences in Industrial Regions - Aralova, N.I.; Klyuchko, O.M.; Mashkin, V.I.; Mashkina, I.V. (Cybernetics and computer engineering, 2021)
Purpose of the paper is to create a mathematical model of functional respiratory system, which simulates the influence of external environment on the parameters of selforganization of human respiratory system in the dynamics of respiratory cycle; and thus to predict hypoxic conditions during tissue damage by hydrocarbons. Results. The mathematical model for respiratory gases transport and mass transfer in human organism is represented as a system of differential equations, which is a controlled dynamic system, and the states of which are determined by oxygen and carbon dioxide stresses in each structural link of the respiratory system (alveoli, blood, and tissues) at each moment of time. The model is supplemented by the equations of transport of the substances in each structural link as well as by the mathematical model of organism oxygen regimes regulation. The model includes seven groups of tissues - brain, heart, liver and gastrointestinal tissues, kidneys, muscle tissue etc. The algorithm of the work and iterative procedure of research with application of suggested complex are given. Мета. Побудувати математичну модель функціональної системи дихання, яка імітує вплив зовнішнього середовища на параметри самоорганізації системи дихання людини в динаміці дихального циклу і таким чином дає змогу прогнозувати гіпоксичні стани внаслідок ураження тканини вуглеводнями. Результати. Надано математичну модель транспорту та масообміну респіраторних газів в організмі людини як систему диференційних рівнянь, яка є керованою динамічною системою, стани якої визначаються у кожен момент часу рівнями напруження кисню та вуглекислого газу в кожній структурній ланці системи дихання (альвеолах, крові, тканинах). Модель доповнено рівняннями транспорту речовини у кожній структурній ланці і математичною моделлю регулювання кисневих режимів організму. У моделі передбачено сім груп тканин — тканини мозку, серця, печінки та ШКТ, нирок, м’язові тканини тощо. Наведено алгоритм роботи та ітераційну процедуру дослідження із застосуванням запропонованого комплексу.